Middle term results of tantalum acetabular cups in total hip arthroplasty following pelvic irradiation - De Paolis, Massimiliano (Acta Orthop Traumatol Turc, 2019)
OBJECTIVES: The aim of this study was to evaluate the middle term cup survival, assess the functional implementation and the radiographic evolution of tantalum acetabular cups implanted on patients with a history of pelvic radiotherapy. METHODS: From 2005 to 2013, we performed 12 THA replacements (4 males 8 females; mean age: 46.6 years (range 25–75)) on irradiated bone with Trabecular metal acetabular cups, 8 primary implants and 4 revision implants. The mean radiation dose delivered was 5500 cGy (range 3000 cGy–13,600 cGy). The mean follow-up was 68 months, ranging from 38 to 136. Postoperative follow-up time was assessed at 1, 3, 6 and 12 months, then annually. Double projection radiographs were requested at each control. Radiographic signs of loosening were investigated by X-rays looking for radiolucent lines. We used the Harris hip score for the clinical and functional evaluation. RESULTS: To now none of the 12 patients in the series needed any revision surgery for aseptic loosening. In the revision group one patient have been revised for septic loosening, two patients have been treated by conservative procedure for hip dislocation. Post-operative Harris hip score improved from an average of 46 points to 85.3 points. At last follow-up we found only in one case radiographic signs of progressive lucent line, without clinical sign of failure. CONCLUSION: In a clinical setting, tantalum cup seems to provide a good stability due to the integration of the trabecular metal to the underline cancellous bone. The reported results, in agreement with literature data, propose the use of tantalum cups in irradiated bone. LEVEL OF EVIDENCE: Level IV, therapeutic study.